Mobile government : an emerging direction in e- government - Kushchu, Ibrahim 1964- (Hershey, Pa. : IGI Pub., 2007)
"This book provides selected examples of current developments from various countries in terms of technology, applications and services, and various real world m-government examples, their evaluations, challenges and opportunities. It contains introductory knowledge on m-Government, and then moves on to a deeper examination of various applications, that are significant in terms of current and future developments in m-Government"
Includes bibliographical references and index
Keywords: Internet in public administration; Internet in public administration -- Case studies; Electronic government information; Electronic public records